Dynamics of Islamic Religious Education Learning for Children with Special Needs at SLB YPPLB Padang City - M Faisal; Rusydi Rusydi; Romiyilhas Romiyilhas; Nurul Huda (Yayasan Adra Karima Hubbi, 2025)
Background. Islamic Religious Education for Children with Special Needs (ABK) plays a crucial role in the formation of inclusive character and spirituality. However, Islamic Religious Education learning for ABK at SLB YPPLB Padang City faces complex challenges, such as the heterogeneity of student needs (mentally retarded, deaf, physically disabled), limitations of conventional methods, and minimal teaching materials and teacher training. Purpose. This study aims to analyze Islamic Religious Education learning strategies, supporting factors, and inhibiting factors at SLB YPPLB. Method. The research used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews with Islamic Religious Education teachers, special needs students, and education personnel, as well as documentation studies. Results. The results of the study show that: 1) Learning planning still adopts standard lesson plans with limited modifications, 2) The learning process is dominated by lecture and drill methods which are less effective, 3) Evaluation tends to be conventional and not fully adaptive, and 4) The main inhibiting factors include limited resources, while collaborative assessments and visual media are potential supporters. Conclusion. The study's conclusions confirm the need for the development of flexible lesson plans, inclusive method-based teacher training, and portfolio-based evaluation. These findings contribute to the integration of Islamic education principles (ta'd?b and tarbiyah) with inclusive education theories (differentiated instruction, scaffolding), while strengthening the urgency of systematic policies for holistic Islamic Religious Education learning for children with special needs. Further research recommendations include multi-location studies and the development of special needs assessment instruments.